The Detection of Different Cancer Types Using an Optimized MoS2-Based Surface Plasmon Resonance Multilayer System - Talia Tene; Diego Fabián Vique López; Paulina Elizabeth Valverde Aguirre; Adriana Monserrath Monge Moreno; Cristian Vacacela Gomez (Sci)
The early and accurate detection of cancer remains a critical challenge in biomedical diagnostics. In this work, we propose and investigate a novel surface plasmon resonance (SPR) biosensor platform based on a multilayer configuration incorporating copper (Cu), silicon nitride (Si3N4), and molybdenum disulfide (MoS2) for the optical detection of various cancer types. Four distinct sensor architectures (Sys1–Sys4) were optimized through the systematic tuning of Cu thickness, Si3N4 dielectric layer thickness, and the number of MoS2 monolayers to enhance sensitivity, angular shift, and spectral sharpness. The optimized systems were evaluated using refractive index data corresponding to six cancer types (skin, cervical, blood, adrenal, breast T1, and breast T2), with performance metrics including sensitivity, detection accuracy, quality factor, figure of merit, limit of detection, and comprehensive sensitivity factor. Among the configurations, Sys3 (BK7–Cu–Si3N4–MoS2) demonstrated the highest sensitivity, reaching 254.64 °/RIU for adrenal cancer, while maintaining a low detection limit and competitive figures of merit. Comparative analysis revealed that the MoS2-based designs, particularly Sys3, outperform conventional noble-metal architectures in terms of sensitivity while using earth-abundant, scalable materials. These results confirm the potential of Cu/Si3N4/MoS2-based SPR biosensors as practical and effective tools for label-free cancer diagnosis across multiple malignancy types.